The Sentencing of Insult and/or Defamation Cases in Indonesia - Djatmika, Prija; Istiqomah, Milda (Arena Hukum, 2025)
This study examines sentencing decisions in cases of insult and/or defamation by employing a mixed-method approach that combines quantitative and qualitative analysis. Quantitative analysis uses district court verdicts from 2016 to 2021 to identify patterns and trends in sentencing, while qualitative analysis delves into aggravating and mitigating factors in judges’ considerations. Compared to previous studies, conducted by Samudra (2019), Ziar (2022), Fatmawati, et al. (2023), Emaliawati (2024), and Nurbaeti (2025), the result of this study shows that most cases end with prison sentences and/or fines. Judges consider various factors such as the severity of the offence, the impact on the victim, and the defendant’s background. Interestingly, there were several cases, particularly those involving corporations, where judges imposed much harsher sentences than the prosecutor’s prosecution, indicating a unique dynamic in the application of justice. From the perspective of judicial independence theory, the judges should exercise their independence in interpreting legal norms and balancing between positive law and substantive justice. Judges are not merely “mouthpieces of the law”; they are active actors in assessing the moral value and social impact of the defendant’s actions. Meanwhile, based on the theory of punishment, the decisions reflect a retributive approach as a form of retribution for reprehensible acts, as well as a preventive approach, to deter perpetrators and the wider community. This study makes an important contribution to understanding the complexity of sentencing in cases of insult and/or defamation and highlights the need for more measurable and consistent sentencing guidelines.